2003
DOI: 10.1063/1.1568729
|View full text |Cite
|
Sign up to set email alerts
|

The ultrafast dynamics of HBr–water clusters: Influences on ion-pair formation

Abstract: The ultrafast dynamics of HBr–water clusters have been investigated using pump–probe spectroscopy coupled with reflectron time-of-flight mass spectrometry. HBr clusters, mixed HBr–water clusters, and protonated water clusters are observed in the mass spectra. Dynamic studies reveal that when an HBr chromophore of a cluster with less than five solvent molecules is excited electronically, solvent reorganization occurs to form the solvent separated ion-pair [S. M. Hurley et al., Science 298, 202 (2002)]. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…Large amount of attention has been paid to the photochemistry of hydrogen halides in water clusters due to their relevance to the ozone depletion process (Hurley et al, 2002 , 2003 ; Dermota et al, 2005 ). Photodissociation in clusters has been also investigated for other relevant species, e.g., OClO (Fenner et al, 1997 ; Kreher et al, 1999 ), and nitric acid (Li and Huber, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Large amount of attention has been paid to the photochemistry of hydrogen halides in water clusters due to their relevance to the ozone depletion process (Hurley et al, 2002 , 2003 ; Dermota et al, 2005 ). Photodissociation in clusters has been also investigated for other relevant species, e.g., OClO (Fenner et al, 1997 ; Kreher et al, 1999 ), and nitric acid (Li and Huber, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Small HX(H 2 O) N clusters represent the ideal system to pursuit this question. Femtosecond pump‐probe spectroscopy showed that N = 5 water molecules were needed to generate the contact ion pair in HBr‐water clusters . Both HCl and HBr in water clusters were investigated by FTIR spectroscopy suggesting the acidic dissociation in the range of N = 3‐5 .…”
Section: Examples Of Atmospheric Cluster Studiesmentioning
confidence: 99%
“…Femtosecond pump-probe spectroscopy showed that N = 5 water molecules were needed to generate the contact ion pair in HBr-water clusters. 258,259 Both HCl and HBr in water clusters were investigated by FTIR spectroscopy suggesting the acidic dissociation in the range of N = 3-5. 260,261 Essentially the same size range for acidic dissociation could be obtained from comprehensive IR-UV experiments and theoretical investigations of small HCl and water clusters by Reisler and Bowman reviewed recently.…”
Section: Hydrogen Halides In Water Clustersmentioning
confidence: 99%
“…pKas for dissociation in aqueous environments, bond lengths in Å, and dipole moments in Debyes (Cotton and Wilkinson, 1988;Weast et al, 1989;Sato and Hirata, 1999). Microsolvation studies of a single acid molecule with one or more water molecules have expanded our understanding of acid dissociation and, in some cases, have pinpointed 4 the number of solvent molecules needed to achieve the formation of the ion pair (Laasonen and Klein, 1994;Schindler et al, 1994;Lee et al, 1996;Ando and Hynes, 1999;Conley and Tao, 1999;Gertner et al, 1999;Cabaleiro-Lago et al, 2002;Devlin et al, 2002;Hurley et al, 2003;Voegele and Liedl, 2003;Kuo and Klein, 2004;Odde et al, 2004;Gutberlet et al, 2009;Vargas-Caamal et al, 2016a). These studies correspond to ideal situations that do not account for crucial factors such as increasing acid concentration via the explicit addition of new molecules.…”
Section: Introductionmentioning
confidence: 99%